Sirtuin 5 inhibits mitochondrial metabolism in liver cancer cells and promotes apoptosis by mediating the desuccinylation of CS - Cao, Huimin; Wei, Dongsheng; Li, Han; Zhao, Mei; Ma, Yixin; Kong, Liang; Sui, Guoyuan; Jia, Lianqun (Frontiers in Immunology, 2025)
BackgroundCitrate synthase (CS) is a key rate-limiting enzyme in the tricarboxylic acid (TCA) cycle and plays a crucial role in cancer progression. However, the mechanism by which CS promotes liver cancer growth remains unclear. The aim of this study is to elucidate the role of CS and its post-translational modifications (PTMs) in the initiation and progression of hepatocellular carcinoma (HCC).MethodsLiquid chromatography-tandem mass spectrometry (LC-MS/MS) was used to detect protein lysine succinylation in human liver cancer and adjacent non-cancerous tissues. A HCC model was established in male C57BL/6 mice through intraperitoneal injection of DEN. The expression of SIRT5 and CS in HCC mice was assessed by RT-qPCR, immunohistochemistry, and Western blotting. HepG2 cells were cultured, and co-immunoprecipitation (Co-IP) was performed to evaluate the interaction between SIRT5 and CS. Western blotting was used to measure the succinylation levels of CS. In addition, Mito-Tracker Red CMXRos staining, reactive oxygen species (ROS) measurement, ATP level assay, EdU cell proliferation assay, colony formation assay, TUNEL staining, and flow cytometry were used to investigate the effects of CS succinylation and desuccinylation on mitochondrial function and cell proliferation in hepatocellular carcinoma cells.ResultsA total of 358 differentially modified proteins were identified in human liver cancer tissues. These differentially modified proteins were primarily enriched in the mitochondria, and CS exhibited high levels of succinylation in HCC tissues. In mouse liver cancer tissues, SIRT5 expression was reduced while CS expression was increased. Furthermore, SIRT5 was found to interact with CS, mediating the de-succinylation of CS at the lysine 375 site. Additionally, succinylation at the K375 site of CS was shown to enhance mitochondrial activity and ATP content in HepG2 cells, while reducing intracellular ROS levels and promoting cell proliferation. In contrast, de-succinylation of CS at the K375 site significantly impaired mitochondrial function and ATP levels, increased ROS levels, and induced apoptosis in HepG2 cells.ConclusionSuccinylation of CS is crucial for maintaining mitochondrial function and promoting cell proliferation in liver cancer cells. Targeting SIRT5-mediated de-succinylation of CS may represent a promising therapeutic strategy for the treatment of hepatocellular carcinoma.